Estimation of soil erodibility factor (K) for soil series in Kuantan river basin - Tan, Chong Qing (2018)
Soil erodibility factor is the indicator of the susceptibility of a soil to raindrop impact, runoff and other erosion processes. It is one of the components of the Universal Soil Loss Equation (USLE) and can be affected by many factors such as soil type, infiltration rate, permeability rate and organic matter content and. In this study, a total of fourteen soil series found in Kuantan River Basin namely Durian-Munchong-Bungor, Malacca-Tavy-Gajah Mati, Holyrood-Lunas, Kuala Brang-Kedah-Serdang, Kranji, Kuantan, Mined Land, Peat, Rudua, Rengam-Bukit Temiang, Rengam-Jerangau, Steepland, Telemong-Akob-Local Alluvium and Urban Land was studied with regards to the composition of soil such as percentage of organic matter, silt, clay and fine sand as well as its specific gravity. With the results, the soil erodibility factor can be computed using the Wischmeier soil erodibility equation and Tew modified soil erodibility equation. The computation shows that K factor computed by Wischmeier was smaller than Tew and Rudua soil series was less erodible. Rudua soil series has the highest percentage of organic matter at 10.98% and the lowest percentage of silt at 0.04% which made it less erodible. In contrast, Peat was more erodible compared to other soil series as it had the highest percentage of silt at 16.38% and with a relatively small amount of organic matter around 5.48%.